Initial experience of left bundle branch area pacing using stylet‐driven pacing leads: A multicenter study. (6th June 2022) - De Pooter, Jan; Ozpak, Emine; Calle, Simon; Peytchev, Peter; Heggermont, Ward; Marchandise, Sebastien; Provenier, Frank; Francois, Bart; Anné, Wim; Pollet, Peter; Barbraud, Cynthia; Gillis, Kris; et al.
Abstract: Background: Left bundle branch area pacing (LBBAP) has been performed exclusively using lumen‐less pacing leads (LLL) with fixed helix design. This registry study explores the safety and feasibility of LBBAP using stylet‐driven leads (SDL) with extendable helix design in a multicenter patient population. Methods: This study prospectively enrolled consecutive patients who underwent LBBAP for bradycardia pacing or heart failure indications at eight Belgian hospitals. LBBAP was attempted using SDL (Solia S60; Biotronik) delivered through dedicated delivery sheath (Selectra3D). Implant success, complications, procedural, and pacing characteristics were recorded at implant and follow‐up. Results: The study enrolled 353 patients (mean age 76 ± 39 years, 43% female). The mean number of implants per center was 25 (range: 5–162). Overall, LBBAP with SDL was successful in 334/353 (94%), varying from 93% to 100% among centers. Pacing response was labeled as left bundle branch pacing in 73%, whereas 27% were labeled as myocardial capture. Mean paced QRS duration and stimulus to left ventricular activation time measured 126 ± 21 ms and 74 ± 17. SDL‐LBBAP resulted in low pacing thresholds (0.6 ± 0.4 V at 0.4 ms), which remained stable at 12 months follow‐up (0.7 ± 0.3, p = .291). Lead revisions for SDL‐LBBAP occurred in 5 (1.4%) patients occurred during a mean follow up of 9 ± 5 months. Five (1.4%) septal coronary artery fistulas and 8 (2%) septal perforations occurred, none of them causing persistent ventricular septal defects. Conclusion: The use of SDL to achieve LBBAP is safe and feasible, characterized by high implant success in low and high volume centers, low complication rates, and stable low pacing thresholds. Abstract : Left bundle branch area pacing (LBBAP) using stylet driven pacing leads (SDL)